Desenvolvimento, caracterização e secagem de sementes com cobertura artificial - Ferreira, Margarete Martins Pereira (Universidade Federal de São Carlos, 2003)
The studies on the preparation and drying of seeds with artificial coat covering promote the integration of the referring research lines for drying of seeds and gel. Thus, the aim of this research were carried out a methodology to promote the coated of seeds with material the base of gel, to characterize the system seed-gel and to realize the search of information about the interaction among particles and fluid during the drying process in a fixed bed. In addition, it was also analyze, before and after each accomplished operation, the effects of the stages involved in the construction of the coated seed on the physiologic quality of them. Millet seeds (Pennisetum glaucum), gel agar and sorbitol were used in the tests. The best mixture was used to coat seeds in order to maintain their physiologic quality and the gel adherence. To them was composed such mixture by 1.5% of gel agar and by 5% of sorbitol in relation to the gel. After the development of the methodology of coating, some analyses were used to characterize the system seed-gel such as: dimensions, sphericity, specific mass, thermal conductivity, thermal diffusivity and specific heat. Due to the high moisture content of the coating material, it was necessary the development of a methodology that accelerated the moisture transfer, for the determination of the equilibrium moisture content of the system seed-gel-air. The best equation to determine the equilibrium of the system it was Chen-Clayton s equation, which presented a good agreement with the experimental data, in the range of temperatures from 25 to 50°C and moisture from 11 to 84% bu. The drying kinetics was obtained in fixed bed of thick layer for temperatures from 30 to 50°C and velocities from 0.5 to 2.5 m/s, The equation fitted the experimental data of drying kinetics better was one proposed by Page. . Tests of convective drying in fixed of thick layer allowed obtaining the maxim thickness of bed to supplies appropriate product to the storage. The immediate and latent effects were evaluated and according to them, the physiologic quality was maintained. Therefore, the system seed-gel satisfied the expectations concern with tests of physical characterization and regeneration of the seeds. However, this system seed-gel was also appropriate for convective drying process in fixed bed of small thickness.
Keywords: Secagem; Recobrimento; Leito fixo; Sementes; Gel; Sementes - qualidade; ENGENHARIAS::ENGENHARIA QUIMICA